2009
DOI: 10.1002/dei.266
|View full text |Cite
|
Sign up to set email alerts
|

Phonological awareness and decoding skills in deaf adolescents

Abstract: This study investigated the phonological awareness skills of a group of deaf adolescents and how these skills correlated with decoding skills (single word and non-word reading) and receptive vocabulary.Twenty, congenitally profoundly deaf adolescents with at least average nonverbal cognitive skills were tested on a range of phonological awareness tasks, and a nonword and real-word reading task, and their speech intelligibility was rated. Scores on a receptive vocabulary measure were gathered from existing reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Gravenstede & Roy, 2009;Harris & Moreno, 2006). Deaf children come from diverse language and communication backgrounds, ranging from native sign language users with deaf parents through to the vast majority who communicate through speech and have hearing parents.…”
mentioning
confidence: 99%
“…Gravenstede & Roy, 2009;Harris & Moreno, 2006). Deaf children come from diverse language and communication backgrounds, ranging from native sign language users with deaf parents through to the vast majority who communicate through speech and have hearing parents.…”
mentioning
confidence: 99%
“…A study in the United States of America by McVilly (2004), reported that learners with hearing impairment often lack friends and experience a lot of loneliness as a result of communication barrier. Good academic results have generally been observed in learners with hearing impairment who are mainstreamed, but they also show higher degrees of isolation and psychological problems due to limited communication (Gravenstede, 2009). This implies that even in the developed countries, learners with hearing impairment are still bound to face some challenges.…”
Section: Introductionmentioning
confidence: 99%
“…A study of EFL for D/HH learners (Domagała-Zyśk & Podlewska, 2019) revealed that students could attain the same level of oral proficiency in the foreign language as in their mother tongue, although aspects related to phonology were challenging (Gravenstede, 2009;Hrastinski & Wilbur, 2016;Marschark et al, 2019). Additionally, several studies have concluded that figurative language was an area in which they struggled on a par with their lexical and syntactical range in their first language and, hence, foreign or second language (Domagała-Zyśk, 2015Dowaliby, 1999;Hrastinski & Wilbur, 2016;Kontra et al, 2015;López Sánchez, 2006;Lund, 2019;Markschark et al, 2009).…”
Section: What We Know About Students With Hearing Impairmentmentioning
confidence: 99%
“…However, the first is nasal, whereas the second and the third are occlusives, which is something that the eye cannot capture. Moreover, /p/ and /b/ also differ in phonation, which is another aspect that is not easily perceived (Atcherson et al, 2017;Ferrández Mora & Villalba Pérez, 1996;Gravenstede, 2009;Markschark et al, 2009). This can be particularly challenging in foreign language teaching when it comes assessing students' pronunciation accuracy and fluency in the language.…”
Section: What We Know About Students With Hearing Impairmentmentioning
confidence: 99%
See 1 more Smart Citation